Incomplete Refractory Kawasaki Disease in an Infant—A Case Report and a Review of the Literature - Mărginean, Cristina O.; Meliț, Lorena E.; Gozar, Liliana; Mărginean, Cristian Dan; Mărginean, Maria O. (Frontiers in Pediatrics, 2018)
Abstract Kawasaki disease (KD) is a febrile vasculitis, which is commonly defined by fever and at least four specific clinical symptoms. Incomplete KD is defined by suggestive echocardiographic findings with an incomplete clinical picture. Refractory KD is diagnosed in patients resistant to intravenous immunoglobulin (IVIG). We report the case of a 6-month-old male infant admitted to our clinic for persistent fever and onset of a generalized polymorphous rash, accompanied by high fever, rhinorrhea, and cough for the past 7 days. The laboratory tests, on the day of admission, revealed leukocytosis with neutrophilia, anemia, thrombocytosis, hypernatremia, hypoalbuminemia, elevated C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Echocardiography showed dilation of the left anterior descending coronary artery (LAD). Based on all these findings, we established the diagnosis of KD, and we initiated IVIG and intravenous pulsed methylprednisolone, with an initial favorable outcome. However, the symptoms reappeared, and we administered a second higher single dose of IVIG, but without any clinical improvement. Moreover, the laboratory parameters and echocardiographic findings worsened. We reinitiated a longer course of intravenous methylprednisolone in a smaller dose, which had a favorable impact on the clinical, laboratory, and echocardiographic parameters. Multiple uncertainties exist related to the management of refractory KD despite the wide spectrum of therapeutic options that have been proposed. Our case demonstrates that in patients refractory to aggressive initial therapy, low or moderate doses of steroid given daily may be helpful. Keywords: Kawasaki disease, coronary aneurysm, methyl-prednisolone, child, refractory form